Activity of Ethanol Fraction of Luffa Acutangula (L.) Roxb. on Cholesterol Reduction in Dyslipidemic Hamster - Viviandhari, Daniek; Prastiwi, Rini; Puspitasari, Elva Fitriani; Perdianti, Pegi (Tropical Biopharmaca Research Center, IPB University, 2020)
National data shows the prevalence of coronary heart disease is 3,6%. The prevalence of dyslipidemia is around 35,9%. Dyslipidemia has a causal relationship with cardiovascular disease. Based on previous research, 70% ethanolic extract of Ridge Gourd has been shown to have antihyperlipidemic activity. This study aimed to study the activity of 70% ethanolic extract fraction of Ridge Gourd in decreasing the levels of total cholesterol, low-density lipoprotein (LDL-C), and triglycerides in hyperlipidemic hamsters. A total of 32 hamster were divided into 8 groups. Negative control, normal control, positive control (using atorvastatin dose 1,24 mg/kg body weight), positive control (fenofibrate dose 12,35 mg/kg body weight), ethyl acetate fraction, n-hexane fraction, water fraction (fraction doses 36,75 mg/kg body weight), and ethanol extract group (extract dose of 240 mg/kg body weight). The results showed that fraction group (n-hexane, ethyl acetate, water) and ethanol extract group experienced a decrease in total cholesterol, LDL-C, and triglycerides levels. Statistical analysis with one-way ANOVA showed an effect on the treatment given (p = 0,005). Tukey's test showed that ethyl acetate fraction group had an effect comparable to positive control with a decrease in total cholesterol, LDL-C, and triglycerides level by 56,03%, 52,14%, and 59,51% consecutively. Ethyl acetate fraction (doses 36,75 mg/kg body weight) was the most effective fraction in reducing total cholesterol, LDL-C, and triglycerides.